Luther and Justification. Issue 2 (June 2017) - Pedersen, Else Marie Wiberg
Abstract: In this article, I reflect on Luther's doctrine on justification as it came out in different ways in some of his seminal writings between 1518 and 1538, all represented in volume 2 of The Annotated Luther . Discovering the righteousness of God as something already given to humans opened fundamentally new perspectives to Luther.